Developing an Accounting System: Under the Macroeconomic and Microeconomic Model of Economic Relations between Business Entities. Example of Hospitality Management - TOVMA, Nataliya; NURGALIEVA, Gulnar; DZHAKISHEVA, Urasgul; KUPENOVA, Zhulduz; USSABAYEV, Arman; ARISTAMBAYEVA, Almira (Journal of Environmental Management and Tourism, 2020)
The ongoing economic reforms in the CIS countries, including Kazakhstan, have highlighted the need for fundamental changes in the accounting practices as well. To achieve the objectives of developing market mechanisms, reforms in the accounting system should be put in the forefront . The need for drastic changes in the organization of accounting has been driven by the development of new economic relations between business entities in the context of transitioning from a centralized economic system to a market economy. The process of development and implementation of new accounting regulations in Kazakhstan has been complicated by the lack of systematic studies on improving accounting in the conditions of market relations, the lack of research into ways of overcoming significant differences in the accounting systems that had historically evolved under a centralized system and market economy.